Pengaruh Kompensasi, Lingkungan Kerja dan Beban Kerja terhadap Kepuasan Kerja Karyawan Koperasi Simpan Pinjam dan Pembiayaan Syariah BMT Muamalat Jumapolo - Nova Vauzira Muvidah; Lamidi Lamidi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the significant influence of compensation, work environment, and workload on the job satisfaction of employees at the Sharia Savings and Loan Cooperative and Financing BMT Muamalat Jumapolo. This research uses quantitative data, with primary data sources. The population in this study consists of 97 employees of the Sharia Savings and Loan Cooperative and Financing BMT Muamalat Jumapolo. The sampling technique used is a census technique, so the entire population is used as the sample. The data analysis techniques used in this study are descriptive analysis, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R2).The results of this study indicate that compensation (X1) does not have a significant influence on the job satisfaction of KSPPS BMT Muamalat Jumapolo employees. The work environment (X2) does not have a significant influence on the job satisfaction of KSPPS BMT Muamalat Jumapolo employees. Workload (X3) has a significant influence on the job satisfaction of KSPPS BMT Muamalat Jumapolo employees. The F-test results show a significant value of 0.000, meaning the model is appropriate for predicting the influence of compensation, work environment, and workload on job satisfaction. The R2 test results indicate that 37.1% of the variation in job satisfaction is explained by these variables, while the remaining 62,9% is explained by other variables outside the model, such as leadership style, work stress, organizational culture, and work discipline.